A study on linguistic features of poem titles in english and vietnamese (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study investigated the linguistic features of poem titles in English and Vietnamese. With analysis of 170 poem titles in English and 170 poem titles in Vietnamese which are collected through the Internet, books and magazines, the study shows that poem titles have remarkable syntactic, semantic and lexical features and there are some similarities and differences between English and Vietnamese. The study conducted based on the combination of a variety of methods such as qualitative, quantitative and comparative methods. In terms of syntax, both English and Vietnamese poem titles are structured in the forms of phrases, dependent clauses and sentences. However, in each structural type, some differences are found. In terms of semantic features, poem themes are recognized in the two languages, including “Pair Love”, “Friendship”, “Family”, “War”, “Women”, “Children”, “Places”, “Nature - Human”, “Loneliness”, “School”, “Heroes”, “Patriotism”. In the corpus of the study, poems about “Children” and “Loneliness” are listed in English only. Whereas the themes of “School”, “Heroes” and “Patriotism” appear in Vietnamese only. In terms of lexical features, certain differences can be seen in the patterns of word formation and lexical choice, except for compounding and simple words, which are used in both English and Vietnamese song titles. Based on the findings and results of this study, some implications for the teaching and learning of English will also be suggested. Hopefully, the result of the study can be somewhat beneficial for the teaching and learning of English. This study may also be helpful for the readers of English